2019
DOI: 10.1101/549279
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial metabolites mediate bumble bee attraction and feeding

Abstract: 16Animals such as bumble bees use chemosensory cues to localize and evaluate essential 17 resources. Increasingly, it is recognized that microbes can alter the quality of foraged resources 18 and produce metabolites that act as foraging cues. The distinct nature of these sensory cues 19 however and their use in animal foraging remain poorly understood. Here, we test the hypothesis 20 that species of nectar-inhabiting microbes differentially influence pollinator attraction and 21 feeding via microbial metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Indeed, recent investigations have demonstrated that the surface of pollen grains is colonised by a diverse community of microorganisms (F€ urnkranz et al, 2012;Ambika Manirajan et al, 2016;Kim et al, 2018;Manirajan et al, 2018); however, the impact of this microbiota on plant fitness is unknown. In nectar, colonisation by bacteria and yeast affects carbohydrate, amino-acid and secondary metabolite composition (Herrera et al, 2008;Peay et al, 2012;Vannette & Fukami, 2016;Rering et al, 2018), with negative or positive impacts on pollinator attraction (Vannette et al, 2012;Schaeffer et al, 2019). It is possible that pollen-colonising microorganisms affect pollen composition in similar ways.…”
Section: Antimicrobial Hypothesismentioning
confidence: 99%
“…Indeed, recent investigations have demonstrated that the surface of pollen grains is colonised by a diverse community of microorganisms (F€ urnkranz et al, 2012;Ambika Manirajan et al, 2016;Kim et al, 2018;Manirajan et al, 2018); however, the impact of this microbiota on plant fitness is unknown. In nectar, colonisation by bacteria and yeast affects carbohydrate, amino-acid and secondary metabolite composition (Herrera et al, 2008;Peay et al, 2012;Vannette & Fukami, 2016;Rering et al, 2018), with negative or positive impacts on pollinator attraction (Vannette et al, 2012;Schaeffer et al, 2019). It is possible that pollen-colonising microorganisms affect pollen composition in similar ways.…”
Section: Antimicrobial Hypothesismentioning
confidence: 99%